Pembentukan Bank Sampah Dan Pemanfaatan Sampah Rumah Tangga Menjadi Pupuk Organik Cair - Latifa Siswati; Neng Susi; Enny Insusanty (Universitas Lancang Kuning, 2022)
People tend to throw garbage even though garbage has a fairly high economic value. Utilization of waste by separating organic and anorganic waste. Anorganic waste in the form of plastic, bottles, paper and others, can be stored in the form of money through a waste bank. Meanwhile, organic waste can be processed into compost. The community in Keranji Guguh Village did not yet have a Waste Bank. Waste Bank was established by means of each house sorting organic and anorganic waste, utilizing household domestic waste, by making Liquid Organic Fertilizer. The targets in this activity are housewives and the people of Kampung Keranji Guguh. The methods used are awareness, counseling, demonstration, and evaluation. There has been an increase in understanding of processing organic waste into Liquid Organic Fertilizer by 80% to 100%, with an average increase of 98%. The results of making Liquid Organic Fertilizer can be used for plant fertilizers, thereby reducing spending on buying fertilizer.